Prevalence and associated risk factors of Helicobacter pylori infection in the Wuwei cohort of north‐western China. Issue 3 (20th December 2020) - Zhang, Fuhua; Pu, Ke; Wu, Zhengqi; Zhang, Zhiyi; Liu, Xin; Chen, Zhaofeng; Ye, Yuwei; Wang, Yuping; Zheng, Ya; Zhang, Jinhua; An, Feng; Zhao, Shijun; et al.
Abstract: Objectives: To evaluate the prevalence of Helicobacter pylori infection and risk factors and to serotype the strains in Wuwei, located in north‐western China, which has a high incidence of gastric cancer. Methods: Helicobacter pylori infection was analysed in 21 291 adults by 14 C‐urea breath test, and H. pylori antibody were detected in 9183 serum samples by latex immunoturbidimetric method. The correlation of H. pylori infection with demographic–economic, lifestyle factors and medical history among the participants was determined by questionnaire. The antibodies against H. pylori urease, VacA and CagA in serum were determined by dot immunobinding assay. Results: The infection rate of H. pylori was 53.0%, and 90.1% of strains were type I strains. The H. pylori infection rate was higher among farmers (OR = 1.34, 95% CI: 1.19–1.50) and individuals who had a junior high school or higher education level (OR = 1.10, 95% CI: 1.06–1.15), and was lower in older individuals (OR = 0.86, 95% CI: 0.83–0.90), individuals with high income (OR = 0.93, 95% CI: 0.90–0.95), individuals with a habit of eating quickly (OR = 0.93, 95% CI: 0.87–0.99) and individuals who consumed more fruit and vegetables (OR = 0.90, 95% CI: 0.85–0.95). Individuals with history of cholecystitis/cholecystolithiasis, hypertension and asthma were negatively correlated with H. pylori infection ( P < 0.05). Conclusion: The prevalence of H. pylori infection is high in Wuwei. The major prevalent strain is type I strain. Age, education, occupation, household income, consumption of fruit and vegetables, and habit of eating quickly are independent risk factors for H. pylori infection, which is also associated with individuals with a history of extragastric diseases. Abstract : Objectifs: Evaluer la prévalence de l'infection à Helicobacter pylori et les facteurs de risque et déterminer le sérotype des souches à Wuwei, situé dans le nord‐ouest de la Chine, où l'incidence du cancer gastrique est élevée. Méthodes: L'infection à H. pylori a été analysée chez 21.291 adultes par un test respiratoire à l'urée au 14 C, et des anticorps à H. pylori ont été détectés dans 9.183 échantillons de sérum par une méthode immuno‐turbidimétrique au latex. La corrélation entre l'infection à H. pylori et les facteurs démographiques et économiques, le mode de vie et les antécédents médicaux des participants a été déterminée par un questionnaire. Les anticorps contre l'uréase de H. pylori, VacA et CagA dans le sérum ont été déterminés par un test dot par d'immuno‐liaison. Résultats: Le taux d'infection à H. pylori était 53, 0% et 90, 1% des souches étaient du type I. Le taux d'infection à H. pylori est plus élevé chez les agriculteurs (OR = 1, 34 ; IC95%: 1, 19 à 1, 50) et les personnes qui avaient un niveau d'instruction du premier cycle secondaire ou supérieur (OR = 1, 10 ; IC95%: 01, 06 à 01, 15) et était plus faible chez les personnes âgées (OR = 0, 86 ; IC95%: 0, 83‐0, 90), les personnes à revenu élevé (OR = 0, 93 ; IC95%: 0, 90‐0, 95), les personnes ayant l'habitude de manger rapidement (OR = 0, 93 ; IC9 %: 0, 87‐0, 99) et les individus qui consommaient plus de fruits et de légumes (OR = 0, 90 ; IC95%: 0, 85‐0, 95). Les personnes ayant des antécédents de cholécystite/cholécystolithiase, d'hypertension et d'asthme avaient une corrélation négative avec l'infection à H. pylori ( p <0, 05 ). Conclusion: La prévalence de l'infection à H. pylori est élevée à Wuwei. La principale souche répandue est du type I. L'âge, l'éducation, la profession, le revenu du ménage, la consommation de fruits et de légumes et l'habitude de manger rapidement sont des facteurs de risque indépendants d'infection à H. pylori, qui est également associée à des personnes ayant des antécédents de maladies extra‐gastriques.